Sedative Effect of Citronella (Cymbopogon nardus (L.) Rendle) towards Male Mice (Mus musculus) - Yulianita Yulianita; E. Mulyati Effendi; Ekas Mara Firdayani (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Hypnotics are substances which in certain dose is meant for escalating psychological desire to sleep and reduse and causingsleep. The research was aimed to determining the influence and the effective dose of citronella grass as sedative substance applied on male mice. Animals used on the test were amounted to 25 male mice which were divided into 5 groups, each of them consisted of 5 mice. Whose given the citronella grass extract were Dose Group I (12mg/20gBW), Dose Group II (24mg/20gBW), and Dose Group III (48mg/20gBW), by means of Negative Control Group (-) 0,5mL of distilled water, and Positive Group Control (+) in terms of 0.013mL/20gBW Diazepam. The results of the research show that the conferral of citronella grass essence is positively potential as a sedative substance on the mice. Thus, Dose III (48mg/20gBW)becomes the most effective dose with the mice onset of falling recorded 46.7 seconds. The conferral duration of citronella grass essence towards sedative effect on male mice with the dose (III) of 48mg/20gBW is the most effective dose due to the relative similarity with diazepam as postive control, observed from the average duration being close to diazepam as positive control within the average onset amounted to 4.46 seconds, while diazepam itself is amounted to 1.38 seconds.Key words: Citronella Grass, Sedativum, Rotarod